La aplicación de materiales didácticos y su incidencia en el proceso enseñanza-aprendizaje en el bloque curricular “los ciclos de la naturaleza y sus cambios” en el área de ciencias naturales de los estudiantes de cuarto grado de educación general básica de la escuela fiscal Alejandrino Velasco de la ciudad de Loja, durante el año 2014. Lineamientos propositivos - Obelencio Guachizaca, Ángel Patricio (2015)
This research work is on The implementation of teaching materials and their impact on the teaching-learning process in curricular "cycles in nature and its changes" in the area of Natural Sciences of fourth graders of General Education Basic Fiscal Alejandrino Velasco School Loja during 2014. The type of study is descriptive; T he population was composed of 3 teachers, 87 students and one director; Its general objective: to contribute to the analysis on the implementation of the teaching materials used by teachers in the teaching-learning process in the curricular cycles in nature and changes in the area of Natural Sciences of fourth graders General Basic Education Fiscal Alejandrino Velasco School of Loja. In the methodology used, the scientific method to discover the internal relations of the subject, natural and social reality; inductive, determined the specific problem investigated; scenario to test the research hypotheses; and, deductive conclusions. The main conclusion is that using specific teaching materials as a strategy allows the motivation, awakens curiosity, holds the attention and reduces anxiety in students in the teaching and learning of curricular cycles of nature and its changes, when they are making use of audiovisual teaching materials to be more functional; the causes identified, that has not been achieved efficiency of the teaching-learning is the existence of learning disabilities; students can more easily learn when teachers allow them to operate more freely, using active techniques by teaching resources.